2012
DOI: 10.1177/1744629512440783
|View full text |Cite
|
Sign up to set email alerts
|

The mediating impact of coping style on stress perception for parents of individuals with intellectual disabilities

Abstract: Research reveals that parents of individuals with intellectual disabilities experience more stress than parents of persons of normal development. The majority of previous research has measured direct relationships between stress variables and stress perception and little attention has been given to the impact of mediating variables. The present study utilized an indirect pathway model to examine the mediating influence of coping style on the relationship between social support, severity of child disability, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 33 publications
2
16
1
Order By: Relevance
“…Inconsistent with the literature which suggests that mothers experience poorer health outcomes than fathers (Olsson & Hwang, 2001;Samadi, McConkey, & Bunting, 2014), the current study found that being female was associated with more positive outcomes of family-related stress. Much of the evidence which contradicts this finding is, however, derived from studies of families providing care to children and/or individuals with developmental disabilities such as autism (Jones, Totsika, Hastings, & Petalas, 2013;Olsson & Hwang, 2001;Samadi et al, 2014). Little is known about gender-related difference in well-being when the care recipient is an adult.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Inconsistent with the literature which suggests that mothers experience poorer health outcomes than fathers (Olsson & Hwang, 2001;Samadi, McConkey, & Bunting, 2014), the current study found that being female was associated with more positive outcomes of family-related stress. Much of the evidence which contradicts this finding is, however, derived from studies of families providing care to children and/or individuals with developmental disabilities such as autism (Jones, Totsika, Hastings, & Petalas, 2013;Olsson & Hwang, 2001;Samadi et al, 2014). Little is known about gender-related difference in well-being when the care recipient is an adult.…”
Section: Discussioncontrasting
confidence: 94%
“…Satisfaction with support was associated with lower burden and more positive gains. Previous research provides support for these findings, which have demonstrated that the adoption of active or problem‐focused coping and appropriate support can act to buffer the effects of daily stressors (Grant & Whittell, ; Grant et al., ; Llewellyn et al., ; Peer & Hillman, ). This finding may also provide further support for gender based difference in health outcomes of family carers.…”
Section: Discussionmentioning
confidence: 81%
“…The parents of these children face the difficulty of balancing parental usual tasks with the complex care needs of their children (treatment programmes, additional physical duties, etc. ), and needing to adjust emotionally to their child not living up to their expectations (Cassidy et al 2008;Hastings & Beck 2004;Jones & Passey 2004;Paster et al 2009;Peer & Hillman 2012;Twoy et al 2007). However, the specific conditions that contribute to a higher stress level are not always agreed upon in scientific literature (Grant & Whittell 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The LOT‐R has been used repeatedly with parents of children with DD, with these studies finding acceptable reliability and validity with this population (e.g. Baker et al , ; Peer & Hillman, ; Ellingsen et al , ). Cronbach's alpha for the LOT‐R in this sample is α = 0.84, indicating good internal consistency (Bland & Altman, ).…”
Section: Methodsmentioning
confidence: 99%
“…This measure has been used extensively with families who have children with DD (e.g. Bagner & Graziano, 2013;Peer & Hillman, 2012;Tervo, 2010;Webster et al, 2008).…”
Section: Parenting Stressmentioning
confidence: 99%